2008
DOI: 10.1038/sj.bjp.0707611
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin exacerbates isoniazid‐induced toxicity in human but not in rat hepatocytes in tissue‐like cultures

Abstract: Background and purpose: Rifampicin has been extensively reported to exacerbate the hepatotoxicity of isoniazid in patients with tuberculosis. However, this was controversially claimed by previous reports using rat models. This study evaluated the effect of rifampicin on isoniazid-induced hepatocyte toxicity by using human and rat hepatocytes in tissue-like culture. Experimental approach: Hepatocytes in tissue-like gel entrapment were used to examine isoniazid toxicity, as shown by cell viability, intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 35 publications
(48 reference statements)
1
31
0
Order By: Relevance
“…Precisely how such a reactive intermediate induces hepatocyte damage remains to be elucidated, as do the reasons for the increased incidence of hepatotoxicity when combination therapy is used. However, it has been found that rifampicin exacerbates INH-induced toxicity in human though not in rat hepatocytes (Shen et al 2008). In another study, GST-T1 homozygous null polymorphism was found to be a risk factor for antituberculosis drug-induced hepatotoxicity in humans (Leiro et al 2008).…”
Section: Isoniazidmentioning
confidence: 98%
“…Precisely how such a reactive intermediate induces hepatocyte damage remains to be elucidated, as do the reasons for the increased incidence of hepatotoxicity when combination therapy is used. However, it has been found that rifampicin exacerbates INH-induced toxicity in human though not in rat hepatocytes (Shen et al 2008). In another study, GST-T1 homozygous null polymorphism was found to be a risk factor for antituberculosis drug-induced hepatotoxicity in humans (Leiro et al 2008).…”
Section: Isoniazidmentioning
confidence: 98%
“…A few studies have shown that hepatic CYP2E1 activity highly correlates with INH-induced hepatotoxicity (15,17). Previous studies have described that the synergistic effects of RIF contribute to INH-induced hepatotoxicity, probably through the induction of CYP2E1, amidase, or other enzymes (17,(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, they found that in gel entrapment cultures, isoniazid was toxic to both rat and human hepatocytes, especially the latter. This previous study by Shen et al (2008) demonstrates that primary human hepatocytes in gel entrapment culture would be a more effective model for the prediction of drug hepatotoxicity, as well as drug-drug interactions, by establishing a good correlation between in vitro and in vivo test systems. Comparative studies using hepatic models are the most useful for demonstrating species differences in the metabolism of a given drug candidate (Lewis et al, 1998;Lin, 1998;Bun et al, 1999), and are of great value in the judicious and justifiable selection of animals for subsequent pharmacokinetic and toxicological studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still the hypothesis that this could be due to the rapid loss of liver-specific functions of the rat hepatocyte monolayers, especially of CYP450 activity. To resolve this question, new studies can be proposed, using primary human hepatocytes in tissuelike gel entrapment culture or rat hepatocytes entrapped in collagen gel as well as cytocompatible hollow fibers, which maintain liver-specific functions at higher levels and for a long time (Shen et al, 2008). Shen et al (2008) showed that rat and human hepatocytes in monolayer cultures treated with the antituberculosis drug isoniazid did not show any decrease in cell viability or decrease in GSH content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation